The combinatorial effect of age and biological sex on alloimmunity and transplantation outcome - Martin, Friederike; Xiao, Yao; Welten, Vanessa; Nakamori, Keita; Gizlenci, Merih; Zhou, Hao; Tullius, Stefan G. (Frontiers in Transplantation, 2024)
Both, age and biological sex affect transplantation outcomes. We have recently shown in a large volume clinical analysis utilizing the SRTR data that graft survival is inferior in young female kidney transplant recipients. In this multi-factorial analysis, older female recipients presented with a trend towards improved transplant outcomes compared to both young female recipients and male recipients of any age. Those data supported by reports of those of others suggest that sex and age impact alloimmune responses both, individually and synergistically.Biological sex and hormone levels change throughout a lifetime with recognized effects on longevity in addition to an impact on the development and course of several disease preconditions. Detailed mechanisms of those sex and age-specific aspects have thus far been studied outside of transplantation. Effects on alloimmunity are largely unknown. Moreover, the combinatorial impact that both, biological sex and age have on transplant outcomes is not understood.Here, we summarize available data that analyze how age in combination with biological sex may shape alloimmune responses and affect transplant outcomes.